2021
DOI: 10.37934/cfdl.13.9.2841
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Analysis of Thermal Mixing Characteristics of Fluids Flowing Through a Converging T-junction

Abstract: Temperature fluctuation occurs while mixing of hot and cold fluids in a T-junction due to incomplete thermal mixing. This temperature fluctuation can produce thermal fatigue at the weld area of the T-junction. The present study aims to numerically investigate the thermal mixing characteristics of hot and cold fluids in a T-junction. The realizable k-ε turbulence model is used with natural gas as the working fluid. Temperature distribution, mixing quality, and intensity of temperature fluctuation are evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Numerous studies have been conducted to investigate hydrodynamics and mixing characteristics of inline mixers, especially T-type inline mixers, using experimental approaches [7][8][9][10][11]. Utilization of CFD analysis has been proven to improve the understanding of hydrodynamics and mixing phenomena happening inside inline mixers as presented by several previous studies [7,8,[12][13][14][15][16][17]. Based on those works, it can be concluded that different flow parameters influence the hydrodynamic condition in inline mixers, including the angle between the branch and main pipe, diameter ratio, velocity ratio, and mass flow rate.…”
Section: Introductionmentioning
confidence: 99%

Numerical Investigation of Hydrodynamics in Inline Mixers

Maulana Gilar Nugraha,
Daffa Dewa Saputra,
Khairullah Ilyas
et al. 2023
CFDL
“…Numerous studies have been conducted to investigate hydrodynamics and mixing characteristics of inline mixers, especially T-type inline mixers, using experimental approaches [7][8][9][10][11]. Utilization of CFD analysis has been proven to improve the understanding of hydrodynamics and mixing phenomena happening inside inline mixers as presented by several previous studies [7,8,[12][13][14][15][16][17]. Based on those works, it can be concluded that different flow parameters influence the hydrodynamic condition in inline mixers, including the angle between the branch and main pipe, diameter ratio, velocity ratio, and mass flow rate.…”
Section: Introductionmentioning
confidence: 99%

Numerical Investigation of Hydrodynamics in Inline Mixers

Maulana Gilar Nugraha,
Daffa Dewa Saputra,
Khairullah Ilyas
et al. 2023
CFDL
“…The frequency of temperature fluctuation diminishes as the distance between the mixing outlet and the mixing chamber rises, and thermal mixing increases. [13] 2 A validation study of the aerodynamic behaviour of a wind turbine: Threedimensional rotational case…”
Section: Introductionmentioning
confidence: 99%
“…Many other thermal implications of multiphase flow include forced convection of flows in bifurcation channels (Selimefendigil et al , 2021, 2019). The leading research areas related to this field are the thermal mixing characteristics of fluid flow in the T-junction (Nuruzzaman et al , 2021b, 2021a), hybrid nanofluid convection in bifurcation channels and modeling by using hybrid computational fluid dynamics (CFD) (Kolsi et al , 2021; Selimefendigil and Öztop, 2021). T-junction prominently reduces excessive liquid carryovers projected on downstream equipment (Azzi et al , 2010; Liang et al , 2016; Yang et al , 2017).…”
Section: Introductionmentioning
confidence: 99%